The great divide : unequal societies and what we can do about them - Stiglitz, Joseph E. (W.W. Norton & Company, 2015)
Discusses the causes of inequality, including unjust and irresponsible economic policies and misguided priorities, and offers suggestions to help the United States become a more fair and equitable society. --Publisher's description.